Effects of prenatal exposure to diclofenac sodium and saline on the optic nerve of 4- and 20-week-old male rats: a stereological and histological study. (February 2014) - Çolakoğlu, S; Aktaş, A; Raimondo, S; Türkmen, AP; Altunkaynak, BZ; Odacı, E; Geuna, S; Kaplan, S
Abstract We investigated the effects of diclofenac sodium (DS) on development of the optic nerve in utero. Pregnant female rats were separated into three groups: control, saline treated and DS treated. Offspring of these animals were divided into 4-week-old and 20-week-old groups. At the end of the 4th and 20th weeks of postnatal life, the animals were sacrificed, and right optic nerves were excised and sectioned for ultrastructural and stereological analyses. We demonstrated that both DS and saline produced structural and morphometric changes in the total axon number and density of axons, but decreased the myelin sheath thickness in male optic nerves. All ultrastructural and morphometric features were well developed in 20-week-old rats. We showed that development of the optic nerve continues during the early postnatal period and that some compensation for exposure to deleterious agents in utero may occur during early postnatal life.